A Multicentre, Randomised, Double Blind, Parallel Design, Placebo Controlled Study to Evaluate the Efficacy and Safety of Uthever (NMN Supplement), an Orally Administered Supplementation in Middle Aged and Older Adults - Huang, Hao (Frontiers in Aging, 2022)
Objective: The purpose of the study was to evaluate the anti-aging effect of NMN and its safety in a double-blind, parallel, randomised controlled clinical trial. Methods: The study was carried out on 66 healthy subjects between the ages of 40 and65 years, instructed to take two capsules (each containing 150 mg. of NMN or starch powder) once a day after breakfast for 60 days. Results: At day 30, NAD+/NADH levels in the serum showed a noteworthy increase, i.e., by 11.3%, whereas the placebo group had shown no change at all. At the end of the study, i.e., day 60, the NAD+/NADH levels were increased further by 38% compared to baseline, against a mere 14.3% in the placebo group. In the case of SF 36, at day 60, the Uthever group showed a rise of 6.5%, whereas the placebo group was merely raised by 3.4%. At the end of the study, the mean HOMA IR Index showed a rise of 0.6% among the Uthever group and 30.6% among the Placebo group from baseline. Conclusion: The rise in the levels of NAD+/NADH at day 30 and day 60 illustrated the potential of Uthever to raise the levels of NAD+ in the cells, which is linked to higher energy levels and an anti-aging effect. Increased sensitivity to insulin has also been linked to anti-aging. There was no noteworthy change in HOMA score, in the Uthever group whereas there was a noteworthy rise in the placebo group, demonstrating the anti-aging effect of Uthever as in its absence, the parameters worsened. Clinical Trial Registration: (clinicaltrials.gov), identifier (NCT04228640 NMN).